Improving high school students understanding through cooperative learning on atomic structure material - Prasetyo, Muhammad Hadi; Maharani, Endang Tri Wahyuni (Institute of Computer Science (IOCS), 2024)
The learning of high school chemistry is divided into two phases, E and F. One of the materials in phase E that is difficult for students to understand is atomic structure. The objective of this study is to ascertain the impact of cooperative learning on students' comprehension. The comprehension of learners can be gauged by the outcomes of their learning during cooperative learning. The research was conducted at SMA Negeri 15, Semarang City, Central Java on 10 February 2024. The subject of the research was the entire X2 class of SMAN 15 Semarang in the academic year 2023-2024, comprising 36 students: 18 male and 18 female. The study employed a one-group pretest-posttest design. The objective of this study was to assess the impact of cooperative learning on students' learning outcomes. The study comprised three stages: a pre-test, a treatment period, and a post-test. The students' scores on the pretest ranged from 40.00 to 75.00, while their scores on the posttest ranged from 60.00 to 90.00. The values obtained from the pre-test and post-test were added to the data set and analysed using the normalised gain (N-Gain) test. The N-Gain test results indicated a value of 0.48, which signifies that the students' perception of their understanding of chemical concepts increased when they were taught using a cooperative learning model. Consequently, the endeavour to enhance students' comprehension of chemical concepts pertaining to atomic structure through the utilisation of a cooperative learning model was a resounding success.